Influence of a light meal on routine haematological tests - Lippi, Giuseppe (Edizioni SIMTI - SIMTI Servizi Srl, 2010)
INTRODUCTION: Patient-related variables, such as physical exercise, stress and fasting status are important sources of variability in laboratory testing. However, no clear indications about fasting requirements exist for routine haematological tests, nor has the influence of meals been assessed. METHODS: We studied 17 healthy volunteers who consumed a light meal containing a standardized amount of carbohydrates, protein and lipids. Blood was taken for routine haematological tests before the meal and 1, 2 and 4 hours thereafter. RESULTS: One hour after the meal, neutrophil count and mean corpuscular haemoglobin (MHC) increased significantly, whereas lymphocyte and monocyte counts, red blood cell distribution width, haematocrit, and mean corpuscular volume decreased significantly. A clinically significant variation was only observed for lymphocytes. Two hours after the meal, a significant increase was observed for neutrophils and MCH, whereas lymphocytes, eosinophils, haemoglobin and haematocrit decreased significantly. Clinically significant variations were recorded for lymphocytes, red blood cells (RBC), haemoglobin, haematocrit and MCH. Four hours after the meal MCH was significantly increased, while lymphocytes, eosinophils, RBC, haemoglobin and haematocrit were significantly decreased. Clinically significant variations were recorded for neutrophils, eosinophils, RBC, hematocrit and MCH. CONCLUSION: The significant variation of several haematological parameters after a light meal demonstrates that the fasting time needs to be carefully considered in order to interpret the results of haematological tests correctly.